المشكلات الأسرية وعلاقتها بالتحصيل الدراسي لتلاميذ المرحلة المتوسطة - معمري, إيمان; حاج علي, إيمان (University of Eloued جامعة الوادي, 2023)
ملخص الد ا رسة هدفت الد ا رسة إلى الكشف عن العلَقة بين المشكلَت الأسرية والتحصيل الد ا رسي لدى تلَميذ مرحلة المتوسطة، استخدمنا المنهج الارتباطي، واعتمدنا في جمع البيانات على الاستبيان ويحتوي على خمس مشكلَت )الإهمال الأسري، إساءة المعاملة الأسرية، اللَتوافق بين الوالدين، ضعف المستوى الاقتصادي للأسرة ) وضعف المستوى التعليمي للوالدين( اوستعنا بمقياس د ا رسة بن بعيط وبوحاجب ) 2222 ( ود ا رسة حولي ) 2202 وتأكدنا من الخصائص السيكومترية لهذه المقاييس واشتملت عينة د ا رستنا على 041 تلميذا وتم اختيا رهم ،2222/ بالطريقة الطبقية العنقودية من متوسطة الشهيد أحمد التجاني بمدينة الوادي للسنة الد ا رسية 2222 وتوصلت د ا رستنا إلى أنه توجد علَقة ارتباطية لمشكلتي الإهمال الأسري واساءة المعاملة الأسرية بالتحصيل الد ا رسي للأبناء، بالمقابل لا توجد علَقة ارتباطية لمشكلَت اللَتوافق بين الوالدين وضعف المستوى الاقتصادي للأسرة وضعف المستوى التعليمي للوالدين بالتحصيل الد ا رسي للأبناء. ج Abstract The study aimed to reveal the relationship between family problems and educational achievement of middle school pupils, we used the correlative approach, we based our data collection on the questionnaire, and it contains five problems (family neglect, family abuse, family incompatibility, the parent’s poor educational level) and we utilized study scales of Ben Bait and Bouhajeb (2022) and Houli’s (2019), we made sure of the psychometric properties of these metrics. Our study sample included 146 pupils who were selected by the cluster class method of the Chahid Ahmed Tedjani middle school in the city of El oued for the school year 2022/2023. Our study found that there was a correlation between the problems of family neglect and family abused through the children’s educational achievement. Conversely، there is no correlation between problems of family incompatibility and parent’s poor educational level via children’s educational achievement
مذكرة ماستر في علوم التربية تخصص ارشاد وتوجيه
Keywords: المشكلات الأسرية، problèmes de famille, family problems; التحصيل الدراسي، résultat scolaire, Academic achievement